Growth Performance of French Guinea Fowl Broilers Fed the Probiotics Lactobacillus reuteri and Streptomyces coelicolor - Sarayu Bhogoju; Thyneice Taylor-Bowden; Collins N. Khwatenge; Samuel N. Nahashon (Bacteria)
The continuous use of antibiotics is associated with many complications in the poultry industry. Probiotics have emerged as a viable alternative over the past few decades to counter the adverse effects of antibiotics. No candidate probiotic microorganisms have been fully evaluated in the poultry industry for their effectiveness as potential probiotics in guinea fowls (GFs) compared to chickens. Recently, a metagenome evaluation of GFs in our laboratory revealed a predominance of Lactobacillus reuteri (L. reuteri) and actinobacteria class of bacteria in their gastrointestinal tract. The aim of this study is to evaluate a well-known lactic acid probiotic bacterium (L. reuteri) and a unique probiotic (S. coelicolor) that has not been assessed in any guinea fowl species. In the current study, L. reuteri and Streptomyces coelicolor (S. coelicolor) were selected as probiotic bacteria, encapsulated, and added into French guinea fowl (FGF) feed individually at a concentration of 108 cfu/g or both microorganisms combined each at 104 cfu/g. In an 8-week study, 216-day-old guinea keets were randomly assigned to four dietary treatments as indicated: (1) L. reuteri (108 cfu/g); (2) S. coelicolor (108 cfu/g); (3) mixture of L. reuteri (104 cfu/g) and S. coelicolor (104 cfu/g); and (4) control treatment (no probiotics included). The L. reuteri, S. coelicolor, and L. reuteri + S. coelicolor were added into the feed using wheat middlings as a carrier at a final concentration of 108 cfu/g. The FGFs that were fed diets containing L. reuteri showed improved feed consumption at 3–8 weeks of age (WOA). The guineas fed L. reuteri and S. coelicolor showed a lower feed conversion ratio (FCR), which was significant at 2 and 8 WOA, and a numerically lower 8-week average FCR when compared with other dietary treatments. Differences in body weight gain among all dietary treatments were not significant. This research suggests that L. reuteri and S. coelicolor may have the potential for use as probiotics in FGFs when used in combination or separately.